Experimental Investigation and Theoretical Analysis on the Performance of Tube-Sheet Photovoltaic Thermal (PV/T) Collectors (Journal of Solar Energy Research Updates, 2021)
The PV/T collectors realize the simultaneous output of electricity and thermal energy, which are more efficient than the separated photovoltaic (PV) or solar thermal collectors. In this paper, the electricity generation and thermal collection performances of tube-sheet PV/T collector are studied. The main research contents are as follows: an experimental test system of PV/T collector was built to test the electricity generation and thermal collection performances of tube-sheet PV/T at an inlet water temperature of 30°C. Moreover, the flow resistance test was carried out. In addition, the theoretical heat transfer model was established, and the thermal performance was calculated by theoretical analysis. The experimental data showed that the daily average temperature difference between the PV panel and the inlet water temperature was about 22.5°C. The daily average electrical efficiency was about 9.25%, and the daily average thermal efficiency was about 28.67%. The theoretical analysis of the tube-sheet PV/T model was carried out, and the calculated results were close to the experimental results. The main reason for the large temperature difference between the PV panel and water temperature was that the combined thermal resistance between the PV panel and the absorber plate was large, and reducing the combined thermal resistance could reduce the temperature of the PV panel. The effects of solar irradiance, ambient temperature and spacing of row tubes on the performance of thermal collection were analyzed to optimize the PV/T performance.